Optimizing the Formulation of the Ready to Drink Concentrated Beverage from Russula cf. Rosea Pers extract - KHOUNHOMEZAI, keosotsai; SALITXAY, Timnoy; LOKHAMHEUANG, vonesy; PHOMLATSABOUD , Khantavanh; LATMANEE, Maneesa (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aimed to develop a concentrated beverage using Russula cf. Rosea Pers., assessing its chemical and microbiological properties. The mushroom was heat-extracted and pasteurized in a pressure cooker. The resulting extract was combined with Caesalpinia sappan L. extract, red sugar, sugar, salt, and water, then vacuum-sealed in glass bottles, sterilized, and stored at room temperature for shelf-life analysis. A sensory evaluation was conducted with 50 consumers, mostly male (54%), aged 31–45 (84%), and earning 2,000,000–4,000,000 LAK monthly (84%). No significant differences (p>0.05) were found among samples T1, T2, and T3. However, sample T4 showed a significant difference (p<0.05) and received higher ratings. T4’s sensory scores across various attributes ranged from 7.63 to 8.10, with a 96% acceptance rate and 86% purchase intent, making it the most preferred formulation. So this treatments taken to study shelf life of product by testing sterilization is 121°C used different times, Chemical stability was assessed by monitoring pH and °Brix values. On day 0, pH values were K1=4.88, K2=5.01, and K3=4.9. After 30 days, a slight decrease was observed (K1=4.87, K2=4.99, K3=4.8). °Brix values remained stable (K1=2, K2=2.2, K3=2.1). Microbiological safety was confirmed by testing three sterilization treatments-K1 (121 °C/15 min), K2 (121 °C/17 min), and K3 (121 °C/20 min). No bacterial or fungal growth was detected on days 0 and 30. In conclusion, the beverage, particularly T4, demonstrated high consumer acceptance and maintained chemical and microbiological stability over 30 days. Further studies are recommended to optimize sterilization methods and evaluate long-term storage effects to ensure ongoing product safety and quality.